2021
DOI: 10.1111/ijal.12408
|View full text |Cite
|
Sign up to set email alerts
|

EFL learners’ confidence, attitudes, and practice towards learning pronunciation

Abstract: Although pronunciation is part of the curriculum in many EFL education programs, it is often neglected in instruction. The study's rationale was to fill the literature gap and explore Saudi EFL learners’ confidence, attitudes, and practice towards learning pronunciation. To this end, the study recruited a convenience sample of 336 Saudi EFL learners majoring in English at a university in Saudi Arabia. Statistical analyses were conducted to determine: (i) learners’ pronunciation confidence level; (ii) whether e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 63 publications
0
3
0
Order By: Relevance
“…Since this study found no apparent correlation between pronunciation accuracy and their perception of others' accents, the results can also echo other researchers' findings. Almusharraf also claimed that there isn't a correlation between the learners' production accuracy and perception of phonetic segments in a second language [18]. This phenomenon may be explained by the theory of first language "loyalty," which means confident second language learners may not bring production into conformity with perception for psychological reasons JE Flege [19].…”
Section: Pronunciation Accuracy and Perceptionmentioning
confidence: 99%
See 1 more Smart Citation
“…Since this study found no apparent correlation between pronunciation accuracy and their perception of others' accents, the results can also echo other researchers' findings. Almusharraf also claimed that there isn't a correlation between the learners' production accuracy and perception of phonetic segments in a second language [18]. This phenomenon may be explained by the theory of first language "loyalty," which means confident second language learners may not bring production into conformity with perception for psychological reasons JE Flege [19].…”
Section: Pronunciation Accuracy and Perceptionmentioning
confidence: 99%
“…Other experiments also got similar results. Almusharraf found that if learners have higher confidence than the neutral level in their pronunciation accuracy and hold a highly optimistic attitude towards English native-like pronunciation, they tend to have a more accurate perception of English [18]. The causes are related to language anxiety and linguistic self-confidence [20].…”
Section: Self-confidence and Perceptionmentioning
confidence: 99%
“…The results describe the most and least used techniques for teaching pronunciation at three educational levels and Polish teachers' beliefs about teaching pronunciation. The literature [17] shows that English pronunciation is a part of the educational curriculum but is often neglected in teaching. A sample of learners majoring in English was recruited from a university in Saudi Arabia and statistically analyzed to determine the learners' level of pronunciation confidence, whether attitudes toward pronunciation influence learners' confidence in their pronunciation and learners' reported pronunciation attitudes and practices.…”
Section: Literature Reviewmentioning
confidence: 99%